Peran Organisasi Kemasyarakatan Keagamaan dalam Penanggulangan Kemiskinan : Kasus di GPIB Jemaat ”EKKLESIA” DKI Jakarta dan GPIB Jemaat ”NEHEMIA” Desa Cipayung, Kabupaten Bogor (Indonesian Journal of Theology, 2013)
Reformation was introduced to Indonesia in 1998 but it has not been able to alleviate poverty. Many think that it is the government that holds the greatest responsibility for poverty. In fact, the government is not the only stakeholder in development. The private sector and civil society organizations also play an important role in it. The Protestant Church in West Indonesia (GPIB) as part of civil society organizations seems to play a very strategic role in development, including poverty alleviation. Some studies show that the quality of leadership is one of the factors that determine GPIB’s role in reducing poverty. This is closely related to the creation of people’s character that enables the religious civil society organization to make maximum contributions to reducing poverty. Therefore, the 12S-7C5P-3S-GT Navigation Model may provide the leaders and people of GPIB with guidelines to build their character so that they will be ready and able to play a concrete role in alleviating poverty.